2020
DOI: 10.1002/aelm.202000676
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Terahertz Transistors with the Topological Semimetal Cadmium Arsenide

Abstract: Electronic devices that operate at terahertz frequencies will require new materials that exhibit higher carrier velocities than traditional semiconductors. Calculations show that cadmium arsenide, a 3D topological (Dirac) semimetal, is an excellent candidate for field effect transistors that operate at frequencies above 1 THz. Moreover, such transistors have unique advantages that are enabled by the properties of Dirac electrons. These include predictions of an unprecedented linearity of the transconductance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…As a sanity check, note that a difference in frequency of 20 T suggests that the quantity E F i ≈ (60 meV) 2 , assuming v F = 5 × 10 5 m/s [19]. This is indeed what is observed in Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As a sanity check, note that a difference in frequency of 20 T suggests that the quantity E F i ≈ (60 meV) 2 , assuming v F = 5 × 10 5 m/s [19]. This is indeed what is observed in Fig.…”
Section: Discussionsupporting
confidence: 75%
“…A future direction for future research lies in dual-gated devices, which can disentangle tuning of the carrier density from that of i . That research will be enabled by optimization 035435-8 of the capping layer, gate dielectric [19,28], and device design, and is a critical step toward realizing the quantum spin Hall insulator state in cadmium arsenide.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, topologically protected states have also been observed in thin films of Cd 3 As 2 [10][11][12]. Thus, Cd 3 As 2 is currently being explored for technological applications based on the topological properties, e.g., for optical switches, electronic devices operating at frequencies in the terahertz regime, and high-sensitivity photodetectors [13][14][15]. In addition, Cd 3 As 2 is a prime candidate for applications based on the large magnetoresistance, room-temperature chiral charge pumping, thermoelectric properties, and possible topological superconductivity [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[37] As a result, Cd 3 As 2 channel FETs exhibit extreme high current density. [27,37] It should be noted that although 3D TDSs do not have a bulk bandgap, recent studies indicate that the Dirac nodes become gapped in extremely thin (below 60 nm) films. [44][45][46] Shoron et al have demonstrated ambipolar transport in MBE grown Cd 3 As 2 channel FETs at low temperature, as shown in Figure 3i,j.…”
Section: Field Effect Transistorsmentioning
confidence: 99%